Intellectual property licensing and transactions : theory and practice - Contreras, Jorge L. (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
"Students of intellectual property law are often steeped in the theory and practice of IP litigation. Record labels sue parodists and illegal downloaders, patent owners sue infringers, luxury brands sue counterfeiters, employers sue employees who leak their valuable secrets. All of these cases and the doctrines that they create could lead to a view of the world of intellectual property as a battlefield. Like armaments, firms acquire IP rights solely to attack others, to bludgeon competitors or extract rent from consumers. But this view is wrong. It arises from the unfortunate fact that legal education emphasizes reported judicial decisions over all else, and judicial decisions arise from litigation. The reality, however, is that the vast majority of economic activity involving IP arises from transactions - business arrangements among firms and with consumers and, sometimes, the government"--
The business of licensing -- Ownership and assignment of intellectual property -- The nature of an intellectual property license -- Implied licenses and unwritten transactions -- Confidentiality and pre-license negotiations -- License grant and scope -- Exclusive licenses -- Financial terms -- Development, allocation, and management of IP -- Representations, warranties, and indemnification -- Litigation-related clauses : enforcement, settlement, and dispute resolution -- Term, termination, and breach -- Other licensing terms: the "Boilerplate" -- Academic technology transfer -- Trademark and franchise licensing -- Music licensing -- Consumer and online licensing -- Software, data, and the cloud -- Public licenses : open source, creative commons and IP pledges -- Technical standards : fair, reasonable, and non-discriminatory (frand) licensing -- Bankruptcy and insolvency issues -- Estoppel and no challenge clauses -- First sale and exhaustion -- Intellectual propery misuse -- Antitrust and competition issues -- Intellectual property pools and aggregation.
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Intellectual property; License agreements; Patent licenses